Management Pendidikan Agama Islam dalam Menavigasi Era Modern yang Terancam Degradasi Moral - Wiwin Rif'atul Fauziyati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The purpose of writing this work is to understand the management of Islamic religious education in navigating the modern era which is threatened by moral degradation. This research uses a qualitative approach with data sources from scientific literature, interviews with Islamic religious education experts, and descriptive analysis to understand the role of Islamic Religious Education Management in overcoming the moral degradation of the younger generation in the modern era. Management of Islamic Religious Education plays a crucial role in dealing with the moral degradation of the younger generation by integrating Islamic values in the curriculum. Focus on training teachers as moral role models, extracurricular approaches based on Islamic values, and close collaboration with families and communities. Implementing positive discipline, wise use of technology, and monitoring Islamic religious education programs are key strategies. Involvement in research and development, development of joint action plans, and moral counseling complete proactive steps to address the moral degradation of the younger generation holistically and effectively.